Design, fabrication and characterization of stretchable pressure sensor using aerosol jet printing - Leow, Yong Jie (2018)
Aerosol Jet Printing technique is a new and unique manufacturing technique for creating miniaturized electrical components. Unlike conventional electronics manufacturing techniques, Aerosol Jet Printing do not require any masks. This is because it is an Additive manufacturing technique that uses a stream of gas to guide the flow offunctional inks onto a substrate. Due to this aerodynamic focusing technique, there is no contact in this process other than the substrate where the nanoparticles are deposited on. While most research on the Aerosol Jet Printing is on printing fine and minute electronic components, this project focuses on the usage of the Aerosol Jet Printing to produce stretchable electronics. In this project, a stretchable pressure sensor is designed and printed using the Aerosol Jet Printing Process. After the sensor is printed, the resistance of the sensor is characterized. An increase in the base resistance is seen during the testing of the sensor. A study is then done to correlate the thickness of the sensor in terms of printing layers and the resistance of printed tracks. It is found that at least 10 layers of printing is necessary if a stretchable substrate is expected to undergo a cyclic strain, while 15 layers is recommended if the substrate is expected to undergo a large number of cycles. Finally, the printed sensor is incorporated into an electrical circuit to prove the effectiveness of the Aerosol Jet Printing process for stretchable electronics.